Common Variants in NUS1 and GP2 Genes Contributed to the Risk of Gestational Diabetes Mellitus - Zhang, Tianxiao; Zhao, Longrui; Wang, Shujin; Liu, Juan; Chang, Ying; Ma, Louyan; Feng, Jia; Niu, Yu (Frontiers in Endocrinology, 2021)
Background Recently, NUS1 and GP2 genes were reported to be associated with the risk of type 2 diabetes (T2D) in a Japanese population. Given the sharing of pathogenic contribution from genetic factors between T2D and gestational diabetes mellitus (GDM), we conducted the study to systematically examine the relationship of NUS1 and GP2 genes with the susceptibility to GDM in Chinese Han population. Methods A total of 4,250 subjects comprised of 1,282 patients with GDM and 2,968 controls were recruited, and 20 tag single nucleotide polymorphisms (SNPs) (10 from NUS1 and 10 from GP2) were selected for genotyping. Association analyses were conducted for GDM and its related biomedical indexes including fasting glucose and HbA1c levels. Results Two SNPs, rs80196932 from NUS1 (P=2.93×10-5) and rs117267808 from GP2 (P=5.68×10-5), were identified to be significantly associated with the risk of GDM. Additionally, SNP rs80196932 was significantly associated with HbA1c level in both patients with GDM (P=0.0009) and controls (P=0.0003), while SNP rs117267808 was significantly associated with fasting glucose level in both patients with GDM (P=0.0008) and controls (P=0.0007). Serum levels of protein NUS1 and GP2 were measured for the study subjects, and significant differences were identified among groups with different genotypes of SNP rs80196932 and rs117267808, respectively. Conclusions Our findings indicate that NUS1 and GP2 genes contribute to the risk of GDM, which would help to offer the potential to improve our understanding of the etiology of GDM and, in turn, could facilitate the development of novel medicines and treatments for GDM.